Assessment of Role of Job Components and Individual Parameters on the Raised Blood Pressure in a Noisy Industry - Milad ABBASI; Somayeh FARHANG-DEHGHAN; Saeid YAZDANIRAD; Ahmad MEHRI; Malihe KOLAHDOUZI; Rohollah FALLAH MADVARI; Arash AKBARZADEH; Maryam GHALJAHI (Archives of Acoustics)
The present study aimed to determine the role of job components and individual parameters on the raised blood pressure among male workers of textile industry who were exposed to continuous high noise level. Information of all eligible subjects including demographic and individual characteristics, medical history and job characteristics were obtained by direct interview and referring to the medical records. All blood pressure measurements were done using mercury sphygmomanometer in the morning before work. The 8-hours equivalent A-weighted sound pressure level, the level of blood cholesterol and triglyceride, and noise annoyance was determined for each worker. As the result of weighted regression in path analysis (direct effect), only the work shift did not have a significant effect on blood pressure among the studied variables. It can be seen that variables including the level of triglyceride, cholesterol, and noise exposure have the most direct effects on blood pressure. The results of total effects showed that variables, including using the hearing protection device, age, work experience and visibility of sound source, did not have a significant effect on blood pressure. The results of this study indicate that occupational noise exposure alone and combined with other job components and individual parameters is associated with raised blood pressure. However, noise exposure was probably a stronger stressor for increased blood pressure.